Solid electrolyte and preparation method and application thereof
By coating the polymer on the surface of rigid ceramic particles and mixing it with inorganic electrolyte powder for heating and pressurization, a solid electrolyte with a three-dimensional network structure is formed, which solves the safety hazards of liquid electrolyte lithium-ion batteries and the low preparation efficiency, and achieves the improvement of the mechanical strength and the maintenance of the conductivity of the solid electrolyte.
Patent Information
- Application Number
- CN202510024862.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The existing liquid electrolyte lithium-ion batteries have safety risks, and thermal runaway is difficult to completely avoid, and the preparation method of solid electrolyte is inefficient and difficult to mass production.
By coating the polymer on the surface of rigid ceramic particles, it forms core-shell reinforcement particles and mixes it with inorganic electrolyte powder and heat and pressurizes it, so that the polymer becomes a three-dimensional network structure, densify the solid electrolyte, and improves its mechanical strength.
It has achieved the improvement of the mechanical strength of the solid electrolyte, and has a small impact on the conductivity, effectively solving the problems of battery safety hazards and low preparation efficiency.
Smart Images

Figure BDA0005232716820000081 
Figure BDA0005232716820000091 
Figure BDA0005232716820000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a solid electrolyte and a preparation method and application thereof. Background Art
[0002] Currently, commercial batteries on the market are mainly liquid electrolyte lithium batteries. Due to the flammability of liquid electrolytes and the ease with which diaphragms are pierced by lithium dendrites generated during battery cycling, the safety of lithium-ion batteries has gradually received attention. It is difficult to fundamentally eliminate safety hazards in traditional lithium-ion batteries based on electrolytes. The safety issues of liquid electrolyte lithium batteries are still prominent, and thermal runaway is difficult to completely avoid.
[0003] Solid-state lithium-ion electrolytes are chemically stable and not prone to combustion, so they can effectively reduce the occurrence of safety accidents in lithium-ion batteries. In theory, there is no safety problem. Solid-state electrolytes can generally be prepared by two methods: dry method (PTFE-based) and wet method. Among them, the dry method has a low efficiency, and it is difficult to make the electrolyte sheet thin, and the difficulty of mass production is also high. The adhesive used in the wet method is in contact with the electrolyte particle surface, which has a significant effect on the conductivity, and generally due to the low content of the adhesive (<5%), the mechanical properties are poor. Summary of the invention
[0004] The purpose of the present invention is to provide a solid electrolyte and a preparation method and application thereof. The polymer is coated on the surface of rigid ceramic particles and then mixed with the solid electrolyte for heating and pressurization, so that the polymer is transformed into a three-dimensional network structure, and the solid electrolyte is densified at the same time. The rigid ceramic particles play a role in stress conduction. Further heating causes the low molecular weight polymer to further polymerize, enhancing the strength of the polymer three-dimensional network structure, thereby improving the mechanical strength of the solid electrolyte and having little effect on the conductivity.
[0005] In a first aspect, the present invention provides a solid electrolyte comprising inorganic electrolyte powder, rigid ceramic particles and a polymer three-dimensional network structure, wherein the polymer three-dimensional network structure is coated on the surface of the rigid ceramic particles.
[0006] In some embodiments, the rigid ceramic particles include one or more of Al2O3, SiO2, ZrO2, SiC, BN, Si3N4;
[0007] Preferably, the median particle size D50 of the rigid ceramic particles is 0.1-50 μm.
[0008] In some embodiments, the inorganic electrolyte powder is selected from one or a mixture of the following:
[0009] (1)xLi a B·yC c Dd zP2S5, 0≤x<100, 0≤y<100, 0≤z<100, a=1 or 2, c=1 or 2, d=1, 2 or 5, B is S, Cl, Br or I, C is Li, Si, Ge, P, Sn or Sb, and D is Cl, Br, I, O, S or Se;
[0010] (2)Li 1+x M x Ti 2-x (PO4)3, 0<x<2, wherein M is Al, In, Ge, Ga, Y, Lu or La;
[0011] (3)Li 0.5-3x La 0.5+x TiO3, 0<x<0.15;
[0012] (4)Li 7-x Ln3Z 2-x M x O 12 , 0≤x≤2, wherein M is Zr, Hf, Sn, Nb, Y, W or Ta;
[0013] Preferably, the median particle size D50 of the inorganic electrolyte powder is 0.5-100 μm;
[0014] Preferably, the weight ratio of the inorganic electrolyte powder in the solid electrolyte is 50%-99.9%.
[0015] In some embodiments, the polymer includes styrene-ethylene-butylene-styrene copolymer, styrene-butadiene-styrene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, chlorosulfonated polyethylene, polyisobutylene, butadiene-styrene copolymer, polyacrylate series, polyvinylidene fluoride series, polyarylsulfone series, polyethersulfone series, cellulose, polystyrene series, polycarbonate series, polyvinyl chloride series, polyamide series, polyimide series, polyurethane series, ethylene-vinyl acetate copolymer, polyethylene, polypropylene, polyvinyl alcohol, polylactic acid, polyethylene oxide, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene copolymer, sodium carboxymethyl cellulose, polyphenylene sulfide, polyetheretherketone, polyetherketone and a mixture of one or more of polyetherketone;
[0016] Preferably, the molecular weight of the polymer is less than or equal to 10,000;
[0017] Preferably, the polymer contains 1-5 wt% BPO.
[0018] In some embodiments, the three-dimensional polymer network structure coated on the surface of the rigid ceramic particles has a thickness of 1-50 μm.
[0019] In a second aspect of the present invention, a method for preparing a solid electrolyte is provided, comprising the following steps:
[0020] Step 1, preparing reinforced particles: coating the surface of rigid ceramic particles with polymer to prepare core-shell reinforced particles;
[0021] Step 2, preparing a solid electrolyte: mixing the inorganic electrolyte powder and the core-shell reinforced particles, and then maintaining them at 60-100° C. and 200-300 MPa for 1-2 hours for densification to obtain a densified solid electrolyte;
[0022] Step 3, cross-linking polymerization: the prepared densified solid electrolyte is placed in an environment of 100-150° C. for 4-9 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0023] In some embodiments, the densification temperature is 80-100°C, the pressure is 250-300 MPa, and the time is 1.5-2 h;
[0024] Preferably, the cross-linking polymerization is carried out at a temperature of 140-150° C. and for a time of 8-9 hours.
[0025] In some embodiments, the inorganic electrolyte powder and the core-shell reinforced particles are mixed in one or more ways including mixing in a kneader, an internal mixer, a screw extruder, and a rubber mixer.
[0026] In some embodiments, the rigid ceramic particles include one or more of Al2O3, SiO2, ZrO2, SiC, BN, Si3N4;
[0027] Preferably, the D50 of the granular rigid ceramic particles is 0.1-50 μm;
[0028] Preferably, the inorganic electrolyte powder is selected from one or a mixture of the following:
[0029] (1)xLi a B·yC c D d zP2S5, 0≤x<100, 0≤y<100, 0≤z<100, a=1 or 2, c=1 or 2, d=1, 2 or 5, B is S, Cl, Br or I, C is Li, Si, Ge, P, Sn or Sb, and D is Cl, Br, I, O, S or Se;
[0030] (2)Li 1+x M x Ti 2-x (PO4)3, 0<x<2, wherein M is Al, In, Ge, Ga, Y, Lu or La;
[0031] (3)Li 0.5-3x La 0.5+x TiO3, 0<x<0.15;
[0032] (4)Li 7-x Ln3Z 2-x M x O 12 , 0≤x≤2, wherein M is Zr, Hf, Sn, Nb, Y, W or Ta;
[0033] Preferably, the inorganic electrolyte powder D50 is 0.5-100 μm;
[0034] Preferably, the weight ratio of the inorganic electrolyte powder in the solid electrolyte is 50%-99.9%;
[0035] Preferably, the polymer includes styrene-ethylene-butylene-styrene copolymer, styrene-butadiene-styrene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, chlorosulfonated polyethylene, polyisobutylene, butadiene-styrene copolymer, polyacrylate series, polyvinylidene fluoride series, polyarylsulfone series, polyethersulfone series, cellulose, polystyrene series, polycarbonate series, polyvinyl chloride series, polyamide series, polyimide series, polyurethane series, ethylene-vinyl acetate copolymer, polyethylene, polypropylene, polyvinyl alcohol, polylactic acid, polyethylene oxide, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene copolymer, sodium carboxymethyl cellulose, polyphenylene sulfide, polyetheretherketone, polyetherketone and one or more mixtures of polyetherketone;
[0036] Preferably, the molecular weight of the polymer is less than or equal to 10,000;
[0037] Preferably, the polymer contains 1-5wt% BPO;
[0038] Preferably, the thickness of the three-dimensional network structure of the polymer coated on the surface of the rigid ceramic particles is 1-50 μm.
[0039] The third aspect of the present invention provides a use of the above-mentioned solid electrolyte in the preparation of a lithium battery.
[0040] In summary, the present application includes at least one of the following beneficial technical effects:
[0041] By coating the polymer on the surface of rigid ceramic particles to form core-shell reinforced particles, and then mixing the reinforced particles with solid electrolytes, heating and pressurizing, the polymer is transformed into a three-dimensional network structure, and the solid electrolyte is densified. Since the network polymer is porous, the contact area with the solid electrolyte particles is small, and the conductivity is less affected; in addition, coating the polymer on the rigid ceramic particles is conducive to the powderization and dispersion of the polymer. The rigid ceramic particles play a stress conduction role in the reinforced composite solid electrolyte, improving the mechanical strength of the solid electrolyte. Further heating causes the low molecular weight polymer to further polymerize, enhancing the strength of the polymer three-dimensional network structure. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below by specific embodiments, which do not limit the protection scope of the present invention. Some non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the protection scope of the present invention.
[0043] Example 1
[0044] A solid electrolyte comprises inorganic electrolyte powder, rigid ceramic particles and a polymer three-dimensional network structure, wherein the polymer three-dimensional network structure is coated on the surface of the rigid ceramic particles.
[0045] In some embodiments, the rigid ceramic particles include one or more of Al2O3, SiO2, ZrO2, SiC, BN, and Si3N4; for example, the rigid ceramic particles are Al2O3 rigid ceramic particles, SiO2 rigid ceramic particles, ZrO2 rigid ceramic particles, SiC rigid ceramic particles, BN rigid ceramic particles, Si3N4 rigid ceramic particles, a mixture of Al2O3 rigid ceramic particles and SiO2 rigid ceramic particles, a mixture of ZrO2 rigid ceramic particles and SiC rigid ceramic particles, etc.
[0046] In some embodiments, the median particle size D50 of the rigid ceramic particles is 0.1-50 μm, such as the D50 of the rigid ceramic particles is 0.1 μm, the D50 of the rigid ceramic particles is 10 μm, the D50 of the rigid ceramic particles is 20 μm, the D50 of the rigid ceramic particles is 50 μm, etc.
[0047] In some embodiments, the inorganic electrolyte powder is selected from one or more of the following:
[0048] (1)xLi a B·yC c D dzP2S5, 0≤x<100, 0≤y<100, 0≤z<100, a=1 or 2, c=1 or 2, d=1, 2 or 5, B is S, Cl, Br or I, C is Li, Si, Ge, P, Sn or Sb, and D is Cl, Br, I, O, S or Se;
[0049] (2)Li 1+x M x Ti 2-x (PO4)3, 0<x<2, wherein M is Al, In, Ge, Ga, Y, Lu or La;
[0050] (3)Li 0.5-3x La 0.5+x TiO3, 0<x<0.15;
[0051] (4)Li 7-x Ln3Z 2-x M x O 12 , 0≤x≤2, wherein M is Zr, Hf, Sn, Nb, Y, W or Ta;
[0052] In some embodiments, the inorganic electrolyte powder has a median particle size D50 of 0.5-100 μm;
[0053] In some embodiments, the weight ratio of the inorganic electrolyte powder in the solid electrolyte is 50%-99.9%;
[0054] In some embodiments, the polymer includes one or more of styrene-ethylene-butylene-styrene copolymer, styrene-butadiene-styrene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, chlorosulfonated polyethylene, polyisobutylene, butadiene-styrene copolymer, polyacrylate series, polyvinylidene fluoride series, polyaryl sulfone series, polyether sulfone series, cellulose, polystyrene series, polycarbonate series, polyvinyl chloride series, polyamide series, polyimide series, polyurethane series, ethylene-vinyl acetate copolymer, polyethylene, polypropylene, polyvinyl alcohol, polylactic acid, polyethylene oxide, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene copolymer, sodium carboxymethyl cellulose, polyphenylene sulfide, polyether ether ketone, polyether ketone and polyether ketone; for example, the polymer is a mixture of styrene-ethylene-butylene-styrene copolymer, polyaryl sulfone series, polyether sulfone series, polyphenylene sulfide, polyether ether ketone, polyethylene oxide and acrylonitrile-butadiene copolymer, etc.
[0055] In some embodiments, the molecular weight of the polymer is less than or equal to 10,000; such as the molecular weight is 3,000, 5,000, 7,000, 9,000, 10,000, etc.
[0056] In some embodiments, the polymer contains BPO in an amount of 1-5 wt %, such as 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, and the like.
[0057] In some embodiments, the three-dimensional polymer network structure coated on the surface of the rigid ceramic particles has a thickness of 1-50 μm, such as 1 μm, 5 μm, 15 μm, 25 μm, 35 μm, 50 μm, etc.
[0058] In this embodiment, the polymer is a styrene-ethylene-butylene-styrene copolymer, containing 2wt% BPO, with a molecular weight of 5000, the rigid ceramic particles are Al2O3, with a D50 of 2μm, and the inorganic electrolyte powder is Li 10 Sn 0.7 Si 0.3 P2S 12 Powder, D50: 10μm.
[0059] Example 2
[0060] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0061] Step 1: Prepare reinforced particles
[0062] The polymer is coated on the surface of rigid ceramic particles to prepare core-shell reinforced particles.
[0063] In some embodiments, the rigid ceramic particles are a mixture of one or more of Al2O3, SiO2, ZrO2, SiC, BN, and Si3N4, such as the rigid ceramic particles are Al2O3 rigid ceramic particles, SiO2 rigid ceramic particles, ZrO2 rigid ceramic particles, SiC rigid ceramic particles, BN rigid ceramic particles, Si3N4 rigid ceramic particles, a mixture of Al2O3 rigid ceramic particles and SiO2 rigid ceramic particles, a mixture of ZrO2 rigid ceramic particles and SiC rigid ceramic particles, etc.
[0064] In some embodiments, the median particle size D50 of the rigid ceramic particles is 0.1-50 μm; for example, the D50 of the rigid ceramic particles is 0.1 μm, the D50 of the rigid ceramic particles is 10 μm, the D50 of the rigid ceramic particles is 20 μm, the D50 of the rigid ceramic particles is 50 μm, etc.
[0065] In some embodiments, the polymer is a mixture of one or more of styrene-ethylene-butylene-styrene copolymer, styrene-butadiene-styrene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, chlorosulfonated polyethylene, polyisobutylene, butadiene-styrene copolymer, polyacrylate series, polyvinylidene fluoride series, polyaryl sulfone series, polyether sulfone series, cellulose, polystyrene series, polycarbonate series, polyvinyl chloride series, polyamide series, polyimide series, polyurethane series, ethylene-vinyl acetate copolymer, polyethylene, polypropylene, polyvinyl alcohol, polylactic acid, polyethylene oxide, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene copolymer, sodium carboxymethyl cellulose, polyphenylene sulfide, polyether ether ketone, polyether ketone and polyether ketone, such as the polymer is a mixture of styrene-ethylene-butylene-styrene copolymer, polyaryl sulfone series, polyether sulfone series, polyphenylene sulfide, polyether ether ketone, polyethylene oxide and acrylonitrile-butadiene copolymer, etc.
[0066] In some embodiments, the molecular weight of the polymer is less than or equal to 10,000; such as the molecular weight is 3,000, 5,000, 7,000, 9,000, 10,000, etc.
[0067] In some embodiments, the polymer contains BPO in an amount of 1-5 wt %, such as 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, and the like.
[0068] In some embodiments, the thickness of the polymer three-dimensional network structure coated on the surface of the rigid ceramic particles is 1-50 μm, such as 1 μm, 5 μm, 15 μm, 25 μm, 35 μm, 50 μm, etc.
[0069] In this embodiment, the specific method for preparing core-shell reinforced particles is: dissolving styrene-ethylene-butylene-styrene copolymer (containing 2wt% BPO) with a molecular weight of 5000 in a xylene solution, adding Al2O3 (D50: 2μm) rigid ceramic particles, stirring evenly, and obtaining core-shell reinforced particles with a coating layer thickness of 3μm after drying.
[0070] Step 2: Preparation of solid electrolyte
[0071] The inorganic electrolyte powder is mixed with the core-shell reinforced particles, and then maintained at 60-100°C and 200-300MPa for 1-2h for densification to obtain a densified solid electrolyte. For example, the densification temperature is 60°C, 70°C, 100°C, 75°C, 80°C, 90°C, 100°C, etc.; the densification pressure is 200MPa, 210MPa, 220MPa, 230MPa, 240MPa, 250MPa, 260MPa, 270MPa, 280MPa, 290MPa, 300MPa, etc.; the densification time is 1h, 1.3h, 1.5h, 2h, etc.
[0072] In some embodiments, the inorganic electrolyte powder is selected from one or a mixture of the following:
[0073] (1)xLi a B·yC c D d zP2S5, 0≤x<100, 0≤y<100, 0≤z<100, a=1 or 2, c=1 or 2, d=1, 2 or 5, B is S, Cl, Br or I, C is Li, Si, Ge, P, Sn or Sb, and D is Cl, Br, I, O, S or Se;
[0074] (2)Li 1+x M x Ti 2-x (PO4)3, 0<x<2, wherein M is Al, In, Ge, Ga, Y, Lu or La;
[0075] (3)Li 0.5-3x La 0.5+x TiO3, 0<x<0.15;
[0076] (4)Li 7-x Ln3Z 2-x M x O 12 , 0≤x≤2, wherein M is Zr, Hf, Sn, Nb, Y, W or Ta;
[0077] For example, the inorganic electrolyte powder is Li 10 Sn 0.7 Si 0.3 P2S 12 Powder, Li3PS4 powder, Li 10 GeP2S 12 Powder, Li 11 Si2PS 12 Powder, Li 3.25 Ge 0.25 P 0.75 S4 powder, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 powder, Li3PS4 powder and Li 10 GeP2S 12 Mixture of powders, etc.
[0078] In some embodiments, the inorganic electrolyte powder D50 is 0.5-100 μm; such as the inorganic electrolyte powder D50 is 0.5 μm, the inorganic electrolyte powder D50 is 10 μm, the inorganic electrolyte powder D50 is 25 μm, the inorganic electrolyte powder D50 is 50 μm, the inorganic electrolyte powder D50 is 100 μm, etc.
[0079] In some embodiments, the weight ratio of the inorganic electrolyte powder in the solid electrolyte is 50%-99.9%; such as 50%, 60%, 70%, 80%, 90%, 99.9%, etc.
[0080] In some embodiments, the inorganic electrolyte powder and the core-shell reinforced particles are mixed by one or more of a kneader, an internal mixer, a screw extruder, and a rubber mixer, such as shear mixing by a kneader, mixing by an internal mixer, mixing by a screw extruder, or mixing by a rubber mixer.
[0081] In this embodiment, the specific method of densifying the solid electrolyte is: at room temperature, 90 parts by weight of Li 10 Sn 0.7 Si 0.3 P2S 12 The powder (D50: 10 μm) was shear-mixed with 10 parts by mass of core-shell reinforced particles in a kneader for 1 h, and then maintained at 60°C and 200 MPa for 1 h for densification. The polymer was deformed to form a three-dimensional network structure to obtain a densified solid electrolyte.
[0082] Step 3: Cross-linking polymerization
[0083] The obtained densified solid electrolyte is placed in a 100-150°C environment for 4-9 hours to crosslink and polymerize the low molecular weight polymer to obtain a solid electrolyte. For example, the temperature is 100°C, 110°C, 120°C, 125°C, 130°C, 140°C, 150°C, etc., and the time is 4h, 4.5h, 5h, 5.5h, 6h, 7h, 8h, 9h, etc.
[0084] In this embodiment, the prepared densified solid electrolyte is coated by a roller coater and treated at 110° C. for 5 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0085] Example 3
[0086] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0087] Step 1, preparing reinforced particles: coating the surface of SiO2 (D50: 1 μm) rigid ceramic particles with a molecular weight of 7000 with vinylidene fluoride-hexafluoropropylene copolymer (containing 2 wt% BPO) to obtain core-shell reinforced particles with a coating layer thickness of 1 μm;
[0088] Step 2, preparing a solid electrolyte: at room temperature, 80 parts by mass of Li3PS4 (D50: 5 μm) and 20 parts by mass of core-shell reinforced particles were shear-mixed in an internal mixer for 1.5 hours, and maintained at 90°C and 200 MPa for 1 hour for densification, and the polymer was deformed to form a three-dimensional network structure to obtain a densified solid electrolyte;
[0089] Step 3, cross-linking polymerization: the prepared densified solid electrolyte is placed in an environment of 130° C. for 4 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0090] Example 4
[0091] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0092] Step 1, preparing reinforced particles: coating the surface of ZrO2 (D50: 7 μm) rigid ceramic particles with chlorosulfonated polyethylene (containing 2 wt% BPO) with a molecular weight of 10,000 to obtain core-shell reinforced particles with a coating layer thickness of 5 μm;
[0093] Step 2: Prepare solid electrolyte: At room temperature, 70 parts by mass of Li 10 GeP2S 12 (D50: 15 μm) was shear-mixed with 30 parts by mass of core-shell reinforced particles in a screw extruder for 2 h, and maintained at 100 °C and 300 MPa for 1 h for densification, and the polymer was deformed to form a three-dimensional network structure to obtain a densified solid electrolyte;
[0094] Step 3, cross-linking polymerization: the prepared densified solid electrolyte is placed in an environment of 150° C. for 9 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0095] Example 5
[0096] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0097] Step 1, preparing reinforced particles: coating the surface of SiC (D50: 3 μm) rigid ceramic particles with styrene-butadiene-styrene copolymer (containing 2 wt% BPO) with a molecular weight of 9000 to obtain core-shell reinforced particles with a coating layer thickness of 2 μm;
[0098] Step 2: Prepare solid electrolyte: At room temperature, 95 parts by mass of Li 11Si2PS 12 (D50: 7 μm) and 5 parts by mass of core-shell reinforced particles were shear-mixed in a rubber mixer for 2 h, and maintained at 80 °C and 300 MPa for 1.5 h for densification. The polymer was deformed to form a three-dimensional network structure, and a densified solid electrolyte was obtained;
[0099] Step 3, cross-linking polymerization: the prepared densified solid electrolyte is placed in an environment of 115° C. for 7 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0100] Example 6
[0101] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0102] Step 1, preparing reinforced particles: coating a polyisobutylene copolymer (containing 2 wt% BPO) with a molecular weight of 5000 on the surface of BN (D50: 5 μm) rigid ceramic particles to obtain core-shell reinforced particles with a coating layer thickness of 4 μm;
[0103] Step 2: Prepare solid electrolyte: At room temperature, 60 parts by mass of Li 3.25 Ge 0.25 P 0.75 S4 (D50: 16 μm) and 40 parts by mass of core-shell reinforced particles were shear-mixed in an internal mixer for 1.5 h, and maintained at 90°C and 200 MPa for 1 h for densification. The polymer was deformed to form a three-dimensional network structure, and a densified solid electrolyte was obtained.
[0104] Step 3, cross-linking polymerization: the prepared densified solid electrolyte is placed in an environment of 130° C. for 4 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0105] Example 7
[0106] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0107] Step 1, preparing reinforced particles: coating the surface of Si3N4 (D50: 1 μm) rigid ceramic particles with a polyisobutylene copolymer (containing 2 wt% BPO) having a molecular weight of 3000 to obtain core-shell reinforced particles with a coating layer thickness of 1 μm;
[0108] Step 2: Prepare solid electrolyte: At room temperature, 99 parts by mass of Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3(D50: 6 μm) and 1 mass part of core-shell reinforced particles were shear-mixed in an internal mixer for 1.5 h, and maintained at 70 °C and 200 MPa for 1 h for densification. The polymer was deformed to form a three-dimensional network structure, and a densified solid electrolyte was obtained;
[0109] Step 3, cross-linking polymerization: the prepared densified solid electrolyte is placed in a 100° C. environment for 5 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0110] Effect example
[0111] The tensile properties test and electrochemical impedance spectroscopy test were performed on the solid electrolytes obtained in Examples 2-7. The results are shown in the following table:
[0112]
[0113] As can be seen from the above table, the solid electrolytes prepared in Examples 2-7 of the present invention have high tensile strength and lithium ion conductivity. It can be seen that by coating the polymer on the rigid ceramic particles, it is beneficial to the powderization and dispersion of the polymer. Since the rigid ceramic particles play a stress conduction role in the reinforced composite solid electrolyte, the mechanical strength of the solid electrolyte is improved. In addition, by coating the polymer on the surface of the rigid ceramic particles to form core-shell reinforced particles, and then mixing the reinforced particles with the solid electrolyte, heating and pressurizing, the polymer is deformed into a three-dimensional network structure, and the solid electrolyte is densified at the same time. Since the mesh polymer is porous, the contact area with the solid electrolyte particles is small, and the conductivity is less affected.
[0114] Comparative Example 1 Based on Example 2, the effect of core-shell reinforced particles on the results was investigated.
[0115] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0116] S1. Preparation of solid electrolyte: At room temperature, directly add 90 parts by mass of Li 10 Sn 0.7 Si 0.3 P2S 12 The powder (D50: 10 μm), 0.72 parts by mass of Al2O3 rigid ceramic particles (D50: 2 μm) and 9.28 parts by mass of styrene-ethylene-butylene-styrene copolymer (D50: 3 μm, containing 2 wt% BPO) with a molecular weight of 5000 were shear-mixed in a kneader for 1 hour, and maintained at 60°C and 200 MPa for 1 hour for densification, and the polymer was deformed to form a three-dimensional network structure to obtain a densified solid electrolyte;
[0117] S2. Cross-linking polymerization: The prepared densified solid electrolyte is placed in an environment of 110° C. for 5 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0118] Comparative Example 2 Based on Example 2, the effect of core-shell reinforced particles on the results was investigated.
[0119] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0120] S1. Preparation of solid electrolyte: At room temperature, directly add 90 parts by mass of Li 10 Sn 0.7 Si 0.3 P2S 12 The powder (D50: 10 μm) and 10 parts by mass of Al2O3 rigid ceramic particles (D50: 2 μm) were shear-mixed in a kneader for 1 h and maintained at 60°C and 200 MPa for 1 h for densification. The polymer was deformed to form a three-dimensional network structure, and a densified solid electrolyte was obtained.
[0121] S2. Cross-linking polymerization: The prepared densified solid electrolyte is placed in an environment of 110° C. for 5 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0122] Comparative Example 3 Based on Example 2, the effect of core-shell reinforced particles on the results was investigated.
[0123] A method for preparing a lithium ion solid electrolyte comprises the following steps:
[0124] S1. Preparation of solid electrolyte: At room temperature, directly add 90 parts by mass of Li 10 Sn 0.7 Si 0.3 P2S 12 The powder (D50: 10 μm) and 10 parts by mass of a styrene-ethylene-butylene-styrene copolymer (D50: 3 μm, containing 2 wt% BPO) with a molecular weight of 5000 were shear-mixed in a kneader for 1 hour, and densified at 60°C and 200 MPa for 1 hour. The polymer was deformed to form a three-dimensional network structure, thereby obtaining a densified solid electrolyte.
[0125] S2. Cross-linking polymerization: The prepared densified solid electrolyte is placed in an environment of 110° C. for 5 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
[0126] Comparative Example 4 is based on Example 2 to explore the effect of copolymer components on the results
[0127] A method for preparing a lithium ion solid electrolyte, which is different from Example 1 in that the styrene-ethylene-butylene-styrene copolymer does not contain BPO.
[0128] The tensile properties test and electrochemical impedance spectroscopy test were performed on the solid electrolytes of Comparative Examples 1-4 in the same manner, and the results are shown in the following table:
[0129]
[0130]
[0131] Comparative Example 1 directly mixes the polymer with the inorganic electrolyte powder and the rigid ceramic particles for densification, and the tensile strength and lithium ion conductivity of the obtained solid electrolyte are far inferior to those of Examples 2-7. Comparative Example 2 directly mixes the inorganic electrolyte powder with the rigid ceramic particles alone, and the lithium ion conductivity of the obtained solid electrolyte is similar to that of Examples 2-7, but the tensile strength is lower. Comparative Example 3 directly mixes the polymer with the inorganic electrolyte powder for densification, and the resulting solid electrolyte lithium ion conductivity is similar to that of Examples 2-7, but the tensile strength is also lower. It shows that the core-shell reinforced particles composed of low molecular weight polymers coated on the surface of rigid ceramic particles are conducive to overcoming the problems that pure polymers are difficult to powderize and disperse, and can effectively form a three-dimensional network structure of the polymer and a dual-reinforced structure of rigid ceramic particles. Since the polymer exists mainly in a mesh form, the contact area with the solid electrolyte particles is small, and the conductivity is less affected, therefore, the tensile strength and lithium ion conductivity of the solid electrolyte are improved at the same time.
[0132] The styrene-ethylene-butylene-styrene copolymer used in Comparative Example 4 does not contain BPO, and although the lithium ion conductivity of the obtained solid electrolyte is similar to that of Examples 2-7, the tensile strength is also lower, indicating that the polymer containing BPO can effectively improve the tensile strength of the solid electrolyte.
[0133] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. A solid electrolyte, characterized in that The invention comprises inorganic electrolyte powder, rigid ceramic particles and a polymer three-dimensional network structure, wherein the polymer three-dimensional network structure is coated on the surface of the rigid ceramic particles.
2. The solid electrolyte according to claim 1, characterized in that The rigid ceramic particles are one or more of Al2O3, SiO2, ZrO2, SiC, BN, and Si3N4; Preferably, the median particle size D50 of the rigid ceramic particles is 0.1-50 μm.
3. The solid electrolyte according to claim 1, characterized in that The inorganic electrolyte powder is selected from one or a mixture of the following: (1)xLi a B·yC c D d zP2S5, 0≤x<100, 0≤y<100, 0≤z<100, a=1 or 2, c=1 or 2, d=1, 2 or 5, B is S, Cl, Br or I, C is Li, Si, Ge, P, Sn or Sb, and D is Cl, Br, I, O, S or Se; (2)Li 1+x M x Ti 2-x (PO4)3, 0<x<2, wherein M is Al, In, Ge, Ga, Y, Lu or La; (3)Li 0.5-3x La 0.5+x TiO3, 0<x<0.15; (4)Li 7-x Ln3Z 2-x M x O 12 , 0≤x≤2, wherein M is Zr, Hf, Sn, Nb, Y, W or Ta; Preferably, the median particle size D50 of the inorganic electrolyte powder is 0.5-100 μm; Preferably, the weight ratio of the inorganic electrolyte powder in the solid electrolyte is 50%-99.9%.
4. The solid electrolyte according to claim 1, characterized in that The polymer includes styrene-ethylene-butylene-styrene copolymer, styrene-butadiene-styrene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, chlorosulfonated polyethylene, polyisobutylene, butadiene-styrene copolymer, polyacrylate series, polyvinylidene fluoride series, polyaryl sulfone series, polyether sulfone series, cellulose, polystyrene series, polycarbonate series, polyvinyl chloride series, polyamide series, polyimide series, polyurethane series, ethylene-vinyl acetate copolymer, polyethylene, polypropylene, polyvinyl alcohol, polylactic acid, polyethylene oxide, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene copolymer, sodium carboxymethyl cellulose, polyphenylene sulfide, polyetheretherketone, polyetherketone and one or more mixtures of polyetherketone; Preferably, the molecular weight of the polymer is less than or equal to 10,000; Preferably, the polymer contains 1-5 wt% BPO.
5. The solid electrolyte according to claim 1, characterized in that The thickness of the three-dimensional polymer network structure coated on the surface of the rigid ceramic particles is 1-50 μm.
6. A method for preparing a solid electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1, preparing reinforced particles: coating the surface of rigid ceramic particles with polymer to prepare core-shell reinforced particles; Step 2, preparing a solid electrolyte: mixing the inorganic electrolyte powder and the core-shell reinforced particles, and then maintaining them at 60-100° C. and 200-300 MPa for 1-2 hours for densification to obtain a densified solid electrolyte; Step 3, cross-linking polymerization: the prepared densified solid electrolyte is placed in an environment of 100-150° C. for 4-9 hours to cross-link and polymerize the low molecular weight polymer to obtain a solid electrolyte.
7. The preparation method according to claim 6, characterized in that: The densification process in step 2 is performed at a temperature of 80-100° C., a pressure of 250-300 MPa, and a time of 1.5-2 h; Preferably, the temperature of the cross-linking polymerization in step 2 is 140-150° C. and the time is 8-9 hours.
8. The preparation method according to claim 6, characterized in that: In the step, the inorganic electrolyte powder and the core-shell reinforced particles are mixed in one or more ways including mixing in a kneader, an internal mixer, a screw extruder, and a rubber mixer.
9. The preparation method according to claim 6, characterized in that: In step 1, the rigid ceramic particles are a mixture of one or more of Al2O3, SiO2, ZrO2, SiC, BN, and Si3N4; Preferably, the D50 of the granular rigid ceramic particles is 0.1-50 μm; Preferably, in step 2, the inorganic electrolyte powder is selected from one or more of the following: (1)xLi a B·yC c D d zP2S5, 0≤x<100, 0≤y<100, 0≤z<100, a=1 or 2, c=1 or 2, d=1, 2 or 5, B is S, Cl, Br or I, C is Li, Si, Ge, P, Sn or Sb, and D is Cl, Br, I, O, S or Se; (2)Li 1+x M x Ti 2-x (PO4)3, 0<x<2, wherein M is Al, In, Ge, Ga, Y, Lu or La; (3)Li 0.5-3x La 0.5+x TiO3, 0<x<0.15; (4)Li 7-x Ln3Z 2-x M x O 12 , 0≤x≤2, wherein M is Zr, Hf, Sn, Nb, Y, W or Ta; Preferably, the inorganic electrolyte powder D50 is 0.5-100 μm; Preferably, the weight ratio of the inorganic electrolyte powder in the solid electrolyte is 50%-99.9%; Preferably, in step 1, the polymer is styrene-ethylene-butylene-styrene copolymer, styrene-butadiene-styrene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, chlorosulfonated polyethylene, polyisobutylene, butadiene-styrene copolymer, polyacrylate series, polyvinylidene fluoride series, polyaryl sulfone series, polyether sulfone series, cellulose, polystyrene series, polycarbonate series, polyvinyl chloride series, polyamide series, polyimide series, polyurethane series, ethylene-vinyl acetate copolymer, polyethylene, polypropylene, polyvinyl alcohol, polylactic acid, polyethylene oxide, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene copolymer, sodium carboxymethyl cellulose, polyphenylene sulfide, polyetheretherketone, polyetherketone and a mixture of one or more of polyetherketone; Preferably, the molecular weight of the polymer is less than or equal to 10,000; Preferably, the polymer contains 1-5wt% BPO; Preferably, the thickness of the three-dimensional network structure of the polymer coated on the surface of the rigid ceramic particles is 1-50 μm.
10. Use of the solid electrolyte according to any one of claims 1 to 5 or the solid electrolyte prepared by the preparation method according to any one of claims 6 to 9 in preparing a lithium battery.
Citation Information
Patent Citations
Solid electrolyte membrane and preparation method and application thereof
CN112968208A
Modified ceramic material as well as preparation method and application of composite electrolyte prepared from modified ceramic material
CN114361572A
Composite electrolyte, preparation method and application thereof, and all-solid-state battery
CN117895065A
Optical system
KR102258605B1
Low-cost and low-density solid electrolyte composite for solid-state battery
US20240396077A1